Canine babesiosis: a perspective on clinical complications, biomarkers, and treatment - Köster LS; Lobetti RG; Kelly P (Veterinary Medicine: Research and Reports, 2015)
Liza S Köster,1 Remo G Lobetti,2 Patrick Kelly1 1Department of Clinical Sciences, One Health Center for Zoonoses and Tropical Veterinary Medicine, Ross University School of Veterinary Medicine, St Kitts, West Indies; 2Bryanston Veterinary Hospital, Bryanston, South Africa Abstract: Canine babesiosis is a common tick transmitted disease of dogs worldwide. A number of Babesia sp. can infect dogs and the spectrum is increasing as molecular methods are developed to differentiate organisms. Clinical signs are generally attributed to hemolysis caused by the organisms in the erythrocytes but in some animals with some Babesia spp. there can be an immune mediated component to the anemia and/or a severe inflammatory reaction associated. This complicated form of canine babesiosis is associated with high morbidity and mortality. A variety of clinical markers has been investigated to enable clinicians to provide more accurate prognoses and adapt their treatments which vary according to the infecting species. In this review, we discuss the taxonomy, clinical signs, diagnostic imaging, clinical biomarkers, treatment, and prophylaxis of one of the most common and important diseases of dogs worldwide. Keywords: babesiosis, vector-borne disease, dog